1997
DOI: 10.3109/10799899709036600
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin a Potentiates Receptor-Activated [Ca2+]cIncrease

Abstract: The use of the immunosuppressant cyclosporin A (CsA) is frequently associated with hypertension. Drug-induced local vasoconstriction appears to be responsible for this effect. Using fura-2 and 45Ca2+ efflux techniques, we have examined variations in the cytosolic calcium concentration ([Ca2+]c) in rat aortic smooth muscle cells and have shown that increases in [Ca2+]c after [Arg8]vasopressin, serotonin, endothelin-1 or angiotensin II stimulation were potentiated after preincubation of cells with CsA. This effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…It has been shown that an increase in vasoconstriction by CsA is responsible for both side‐effects (Lamb & Webb, 1987; Rego et al , 1990; Sturrock et al , 1993). We have recently demonstrated that CsA potentiates the cytosolic free Ca 2+ ([Ca 2+ ] c ) increase in response to vasoconstrictor hormones in vascular smooth muscle cells (VSMC) (Lo Russo et al , 1996; 1997). The known pharmacological targets of CsA, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that an increase in vasoconstriction by CsA is responsible for both side‐effects (Lamb & Webb, 1987; Rego et al , 1990; Sturrock et al , 1993). We have recently demonstrated that CsA potentiates the cytosolic free Ca 2+ ([Ca 2+ ] c ) increase in response to vasoconstrictor hormones in vascular smooth muscle cells (VSMC) (Lo Russo et al , 1996; 1997). The known pharmacological targets of CsA, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, other studies emphasized the potential role of different mediators, prostaglandins, endothelins, nitric oxide, TGF-␤, etc. (13,21,24,29,34). However, despite these efforts, the information gathered at the present from the various experimental approaches cannot be assembled in an unifying view of the CsA-induced nephrotoxicity.…”
mentioning
confidence: 99%
“…An early contribution to the recognition of the role of Ca 2ϩ signaling pathway in the generation of toxic effects of CsA came from the demonstration that CsA augmented the receptor stimulated calcium fluxes in isolated hepatocytes (27) and increased [Ca 2ϩ ] i in mesangial cells (39). CsA may also affect the extracellular domain of Ca 2ϩ signaling pathway; the incubation of different cell types with therapeutic doses of CsA is associated with the potentiation of the calcium response upon Ca 2ϩ -coupled receptor engagement (21,24), probably through an upregulation of receptor transcription (2). In addition, CsA may alter the control of intracellular Ca 2ϩ release through ryanodine binding modifications in rat heart (30), and it may stimulate or inhibit the release of Ca 2ϩ from IP 3 -sensitive stores (14,26).…”
mentioning
confidence: 99%
“…An increase in vascular a 1 receptor affinity in response to acute CyA treatment has been demonstrated by Tavares et al (2002). Others have shown that CyA acts, via cyclophilin-or calcineurin-independent mechanisms, at a target upstream of G protein, possibly at the receptor level, to increase inositol phosphate formation and cytosolic calcium concentration (Lo Russo et al 1997). Evidence is also available that shows CyA acts by an intracellular mechanism to elevate phosphatidylinositol, which triggers the vascular response to a 1 -adrenoceptor activation (Tavares et al 2002).…”
Section: Discussionmentioning
confidence: 95%